Original contribution: sleeve gastrectomy reduces soluble lectin-like oxidized low-density lipoprotein receptor-1 (sLOX-1) levels in patients with morbid obesity - Taskin, Halit Eren; Kocael, Ahmet; Kocael, Pinar; Zengin, Kagan; Al, Muzaffer; Sozer, Volkan; Buchwald, J. N.; McGlennon, T. W.; Uzun, Hafize (SPRINGER, 2022)
Background Early diagnosis of subclinical cardiovascular disease (CVD) in patients with morbid obesity is important. We investigated the effects of sleeve gastrectomy (SG) on serum soluble lectin-like oxidized low-density lipoprotein receptor-1 (sLOX-1), oxidized LDL (oxLDL), and other metabolic and inflammatory parameters associated with atherosclerosis in patients with morbid obesity. Methods Body mass index (BMI) measurements and assays of metabolic and inflammatory markers were taken in patients in an SG surgery group and a healthy control group and compared at baseline and 12 months after SG. Correlations with changes in these parameters and variations in sLOX-1 were analyzed. Results Metabolic and inflammatory marker values in the surgery (n = 20) and control (n = 20) groups were significantly different at baseline (p < 0.001). The majority of surgery group biomarker levels significantly decreased with mean BMI loss (- 11.8 +/- 9.0, p < 0.001) at 12 months, trending toward control group values. Baseline albumin level as well as percentage reductions in oxLDL and the cholesterol retention fraction (CRF) were found to be significantly correlated with percentage reduction in sLOX-1 at 12 months following SG. Conclusion Metabolic and inflammatory biomarkers elevated at baseline significantly decreased after SG weight loss. Weight loss induced by SG may limit endothelial damage by reducing levels of oxLDL and LOX-1 as assessed by sLOX-1. These findings suggest that sLOX-1 may function as a marker of atherosclerotic disease states in patients with morbid obesity and that metabolic/bariatric surgery can play a meaningful role in CVD prevention.
Keywords: Bariatric surgery; Obesity; Soluble lectin-like oxidized low-density lipoprotein receptor-1; Oxidized low-density lipoprotein; sLOX-1; oxLDL; LDL RECEPTOR-1; CARDIOVASCULAR RISK; SERUM-ALBUMIN; ATHEROSCLEROSIS; LOX-1; ASSOCIATION; BYPASS; Surgery